Intensification the Role of Parent for Learning Assistance Model at Home in The New Normal Era - Sujarwo Sujarwo; Erma Kusumawardani; Iis Prasetyo; Adin Ariyanti Dewi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This activity aims to carry out a model of children's learning assistance through optimizing the role of parents to be more enthusiastic in facing this new normal era. Not a few parent feel confused and difficult in assisting their children in learning. This research used participatory action research method. The program target of this activity is 30 parent and 15 facilitator from keluarga harapan program. It can be seen that the activities carried out have optimized various parties and can achieve the expected output. Based on the activity , beneficiary families are motivated and have high enthusiasm in spreading the knowledge and skills they have acquired to other families. So, from this activity the community service team highlighted several important things that have been done starting from paying attention to the concept of adult learning, strengthening the focus on social capital and also introducing the importance of peer teaching